To respond or not to respond: The effects of interpersonal goals on responsive Facebook behaviours - Danielle Villoresi; Stephanie Tobin; Jennifer Crocker; Tao Jiang (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace)
Past research indicates that compassionate interpersonal goals are associated with greater responsiveness to others. However, whether this extends to casual friends on social networking sites (SNSs) is unclear. The current research examined the effects of interpersonal goals on the likelihood of responding with one-click reactions, comments, and private messages to mock Facebook posts by casual friends. We also examined responding differences depending on post valence. A 3 (response: one-click reaction, comment, private message) x 2 (self-image goal: low, high) x 2 (compassionate goal: low, high) x 2 (post valence: positive, negative) x 2 (post domain: work, social) mixed-model experimental design tested our predictions among Facebook users (N = 389). Results revealed that either self-image or compassionate interpersonal goals at low levels of the opposing goal increased one-click reactions and comments. Additionally, post valence and domain influenced responding. Compassionate goals increased one-click reactions and comments when responding to positive posts and private messages when responding to negative posts. All response modes were more likely for the negative than positive social post, and one-click reactions and comments were more likely for the positive than negative work post. Our findings provide causal evidence that self-image and compassionate goals can increase responding to casual friends on Facebook. Moreover, whether people respond to Facebook posts can be influenced by SNS contextual factors such as the valence of a post and the varied ways to respond.